2002
DOI: 10.1258/095646202760159666
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of herpes simplex virus, cytomegalovirus and human papillomavirus DNA in semen

Abstract: Herpes simplex virus (HSV-2) and cytomegalovirus (CMV) infections produce brain damage in the newborn, and human papillomavirus (HPV) plays a role in cervical carcinogenesis. To assess the frequency of herpes virus and HPV in semen and its role in transmission, semen from 111 male partners of women with histologically-detected genital HPV infection was analysed for HSV, CMV and HPV infection. We used cell culture to detect HSV and CMV, and polymerase chain reaction (PCR) for HPV. Virological findings in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2
6

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 0 publications
4
23
2
6
Order By: Relevance
“…Among males infected at multiple sites, in only 64.3% of the cases the type detected by PB was representative of the type(s) infecting the patient. This finding is in contrast to those of Aynaud et al, who found the same type in penile/urethral biopsy specimens as in the specimens obtained by SE and UB (3,4), suggesting possible contamination. In this analysis, the presence of a different type(s) in samples obtained by UB and SE than in samples obtained by PB suggested actual multifocal infection involving either the urethra or distant parts of the reproductive tract (21,29).…”
Section: Vol 45 2007 Notes 249contrasting
confidence: 99%
See 1 more Smart Citation
“…Among males infected at multiple sites, in only 64.3% of the cases the type detected by PB was representative of the type(s) infecting the patient. This finding is in contrast to those of Aynaud et al, who found the same type in penile/urethral biopsy specimens as in the specimens obtained by SE and UB (3,4), suggesting possible contamination. In this analysis, the presence of a different type(s) in samples obtained by UB and SE than in samples obtained by PB suggested actual multifocal infection involving either the urethra or distant parts of the reproductive tract (21,29).…”
Section: Vol 45 2007 Notes 249contrasting
confidence: 99%
“…In contrast, sampling by UB resulted in a low detection rate, as has also been found in other studies (4,10), in which the rate of HPV DNA detection by UB ranged from 21% to 37%. Similarly, testing of semen for HPV was not efficacious, with only a 26.6% detection rate, which falls in the range of 23.4% to 39.0% reported in the literature (3,18,21). Even though sampling by UB and SE was less adequate than sampling by UB alone, when associated with the latter method, UB and SE each still contributed to HPV DNA detection; thus, the results from this study would result in the recommendation for parallel testing by PB plus UB or SE, which yielded 100% and 97.2% rates of HPV DNA detection, respectively.…”
Section: Vol 45 2007 Notes 249mentioning
confidence: 86%
“…Its presence and persistence in semen has been reported previously (57)(58)(59)(60). In the current study, CMV was the most frequently detected pathogen in semen of infertility patients (8.7%) with copy numbers ranging from 110 to 12 million.…”
Section: Discussionsupporting
confidence: 72%
“…La existencia de genotipos de bajo y alto riesgo de VPH en el semen ha sido demostrada 51 ; es probable que el semen se pueda contaminar por VPH de localización uretral(al igual que ocurre con Herpesvirus y Citomegalovirus) en el momento de la eyaculación 52 , pero también es cierto que su existencia ha sido detectada en el 18.5% de muestras obtenidas quirúrgicamente durante vasectomías 53 . La consecuencia de estos hallazgos es múltiple, ya que aparte de poder estar implicado en la uretroprostatítis inespecífica, las consecuencias mas importantes son dobles bajo nuestro punto de vista; por un lado, las muestras de séme-nes obtenidas de varones sin aparente VPH pueden ser utilizadas para fertilizaciones in vitro y producir de forma iatrogénica una ETS en la mujer receptora.…”
Section: Clínicaunclassified